O’RTACHA SALMOQLI USULDA MAHSULOT TANNARXI TO’G’RISIDAGI HISOBOT - Xudaynazarova Dilnoza; Abdukarimov Bobur (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article examines the preparation of the production cost report using the weighted average method. The study focuses on the theoretical and practical aspects of product cost calculation, its role in accounting, and the importance of cost measurement methods in financial reporting. In particular, the essence of the weighted average method, its application procedure, and its significance in determining the cost of materials and finished goods in the production process are analyzed. The article also explores the stages of preparing a product cost report based on the weighted average method, practical calculations, and their impact on financial results. The findings show that this method allows for simplified and accurate cost calculation, contributing to a more reliable assessment of the financial condition of an enterprise.